HUBUNGAN KARAKTERISTIK INDIVIDU BIDAN DESA DENGAN KINERJA BIDAN DESA DALAM PENCATATAN DAN PENGOLAHAN DATA PWS-KIA DI KECAMATAN BANYUBIRU KABUPATEN SEMARANG - Pambudi, Ramandhani Dwi Setyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Improving the quality of maternal and child health can be seen from the coverage of each area of work. Basic program of PWS - KIA is the collection and processing of maternal and child health data conducted by midwifes. Midwife’s work on PWS-KIA data collection and processing can be influenced by the individual characteristics of midwife. The purpose of this study was to known the strength of the relationship between individual characteristics with collection and processing of data PWS - KIA in Sub-District Banyubiru District Semarang . This study used a cross-sectional design . The sample of this study all of midwife in Sub-district Banyubiru as much as 9 people. Data were analyzed using descriptive and analytic by using relationship strength test Rank Spearman Correlation (ρs ). The results showed that all the variables of individual characteristics were positively correlated , which means having a meaningful relationship with the collection and processing of data PWS - KIA . The variable characteristics of individuals who have the greatest strength of the relationship is work period with the Rank Spearman correlation coefficient value (ρs ) 0.548 which is in the average category , while the smallest is training with the Rank Spearman correlation coefficient (ρs ) 0.297 which is in a weak category. Advice for health centers to implement special training of PWS-KIA data processing in accordance with the existing guidelines , the midwife coordinator have to firmer to the midwife who did not the collection and processing data PWS - KIA in accordance with existing guidelines , while for midwives who classified old work period have to guidance to the midwife who have work period relatively new and midwife attend spesific training of the collection and processing PWS - KIA .data